A scoping study of Indigenous child welfare: The long emergency and preparations for the next seven generations. (October 2018) - Haight, Wendy; Waubanascum, Cary; Glesener, David; Marsalis, Scott
Abstract: This scoping study yielded 37 empirical studies published in peer-reviewed journals addressing one of the most pressing, sensitive, and controversial issues facing child welfare policymakers and practitioners today: the dramatic overrepresentation of Indigenous families in North American public child welfare systems. These studies indicate that relative to other child welfare-involved families, Indigenous families typically experience intense social challenges in the face of few available services. They also may experience racism when accessing available county, state and provincial child welfare services that undermines trust and engagement. Some promising research suggests that partnerships between government child welfare systems and Indigenous tribes and communities may improve services to struggling families. Given the seriousness of the social justice issues, as well as the sheer volume of empirical research in child welfare, the question of how to strengthen child welfare with Indigenous families clearly is under-researched. Notable gaps in the existing literature include the voices of Indigenous children and parents involved in the child welfare system and attention to cultural variation in child protection beliefs and practices across the many Indigenous communities of North America. More work also is needed to design, implement, and evaluate culturally-based child welfare practices; and examine how to build capacity at the tribal level. Highlights: Few empirical studies address overrepresentation of Indigenous families involved in child welfare systems. Overrepresentation due to relatively intense social challenges and racism Partnerships between government child welfare systems and tribes and Indigenous communities may improve services. Gaps in the literature include the voices of Indigenous children and parents.